Konsep Keamanan Data dalam Jaringan - Riyosnal Putra; Jhon Veri (Journal of Innovative and Creativity, 2025)
In the digital era, data security in networks has become a crucial concern for organizations and individuals. As cyber threats continue to evolve, ensuring the confidentiality, integrity, and availability of data is essential. This article aims to review the concept of data security in networks by highlighting the main components, types of threats, and strategies and frameworks that can be applied. Through a literature study method, this study identifies various technical and policy approaches, including the use of encryption, firewalls, IDS, VPNs, and international security standards such as ISO/IEC 27001, NIST, and COBIT. The results of the study indicate that effective data protection requires the integration of technology, organizational policies, and user training to build a strong and adaptive security system against evolving threats.